Role of gender in the survival outcome of acute phase of major trauma: A nationwide, population-based study. Issue 12 (23rd July 2020) - Lee, Rong-Shou; Lin, Wen-Chi; Harnod, Dorji; Shih, Hsin-Chin; Jeng, Mei-Jy
Abstract : Background: Animal models of trauma have shown that females have better posttraumatic survival; however, results of previous studies on the influence of gender on major trauma patients have been controversial. This study aimed to evaluate the association between gender and survival in major trauma patients. Methods: We retrospectively analyzed patients registered in Taiwan's National Health Insurance Research Database between 2008 and 2012 with the diagnosis codes 800-939 and 950-957 (International Classification of Diseases, ninth revision, clinical modification). Data on gender, age, catastrophic illness, and new injury severity score (NISS) ≥16 were collected for comparing patients' mortality after trauma. Propensity score matching (PSM) was performed to eliminate dissimilarities in age, comorbidities, NISS, and primary traumatic regions between the genders. Results: Among 10 012 major trauma patients included in the study cohort, 28.8% (n = 2880) were women. The PSM patient group consisted of 50% (2876 of 5752) women. Women had a higher 30-day (15.4% of women vs 13.8% of men; p < 0.05) and hospital (16.1% of women vs 14.5% of men; p < 0.05) mortality and lower incidence rates of acute respiratory dysfunction (62.5% of women vs 65.9% of men; p < 0.005) and acute hepatic dysfunction (0.8% of women vs 2.1% of men; p < 0.001). However, the analysis of PSM patient groups showed lower mortality rates in women with moderate trauma (NISS 16–24) in the acute phase within three days (1.4% of women vs 2.7% of men, p = 0.03). Analysis of patients with an NISS of 16–24 who died within three days showed a higher NISS in women than in men (19.7 ± 2.3 vs 18.0 ±1.9, respectively, p <0.05). Conclusion: There is no gender difference in 30-day or hospital mortality among major trauma patients. However, women admitted for moderate major trauma had higher survival within three days of major trauma.